Modulation of the Ganges‐Brahmaputra River Plume by the Indian Ocean Dipole and Eddies Inferred From Satellite Observations. Issue 12 (8th December 2017) - Fournier, S.; Vialard, J.; Lengaigne, M.; Lee, T.; Gierach, M. M.; Chaitanya, A. V. S.
Abstract: The Bay of Bengal receives large amounts of freshwater from the Ganga‐Brahmaputra (GB) river during the summer monsoon. The resulting upper‐ocean freshening influences seasonal rainfall, cyclones, and biological productivity. Sparse in situ observations and previous modeling studies suggest that the East India Coastal Current (EICC) transports these freshwaters southward after the monsoon as an approximately 200 km wide, 2, 000 km long "river in the sea" along the East Indian coast. Sea surface salinity (SSS) from the Soil Moisture Active Passive (SMAP) satellite provides unprecedented views of this peculiar feature from intraseasonal to interannual timescales. SMAP SSS has a 0.83 correlation and 0.49 rms‐difference to 0–5 m in situ measurements. SMAP and in stu data both indicate a SSS standard deviation of ∼0.7 to 1 away from the coast, that rises to 2 pss within 100 km of the coast, providing a very favorable signal‐to‐noise ratio in coastal areas. SMAP also captures the strong northern BoB, postmonsoon cross‐shore SSS contrasts (∼10 pss) measured along ship transects. SMAP data are also consistent with previous modeling results that suggested a modulation of the EICC/GB plume southward extent by the Indian Ocean Dipole (IOD). Remote forcing associated with the negative Indian Ocean Dipole in the fall of 2016 indeed caused a stronger EICC and "river in the sea" that extended by approximately 800 km further south than that in 2015 (positive IOD year). The combination of SMAP and altimeter data shows eddies stirring the freshwater plume away from the coast. Plain Language Summary: The Bay of Bengal receives large quantity of freshwater from the Ganges‐Brahmaputra river during the monsoon. The resulting low‐salinity sea surface has strong implications for the regional climate and living marine resources. In situ observations are too sparse to provide salinity maps in this basin, even every 3 months. In contrast, the SMAP satellite provides maps at 40 km resolution, every 8 days, opening great perspectives for studying salinity in the Bay of Bengal. In this article, we show that SMAP compares well with in situ data, even close to the coast. The Ganges Brahmaputra freshwater plume is transported over 2000 km by the East Indian Coastal Current. We further show that climate variability and mesoscale variability induce strong year‐to‐year variations in the way this freshwater plume expands along the east coast of India. Key Points: SMAP provides unprecedented views of the Ganga‐Brahmaputra freshwater plume on synoptic to interannual time scales The interannual variability of the freshwater plume is modulated by mesoscale eddies and the Indian Ocean Dipole SMAP can help improve the understanding and monitoring of salinity impacts on regional climate, tropical cyclones, and oceanic productivity